The governance in El Salvador: an approach from the government-opposition relationship - Ortega Monche, Nivaria (ECA: Estudios Centroamericanos, 2005)
No abstract available. ECA Estudios Centroamericanos, Vol. 60, No. 677, 2005: 251-259.